2021
DOI: 10.1093/jbcr/irab085
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Characteristics in Patients With Major Burn Injury and Smoke Inhalation

Abstract: This study aimed to evaluate pulmonary function measurements and respiratory muscle parameters in patients with major burn injury and smoke inhalation. The inclusion criteria included patients who were diagnosed with a smoke inhalation burn or a major burn of more than 20% of total body surface area (TBSA). All subjects underwent a pulmonary function test, respiratory muscle strength test, peak cough flow and fluoroscopic diaphragmatic movement measurement, and six-minute walk test before starting pulmonary re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…Together, these data-the most comprehensive assessment of pulmonary function among adults with well-healed burn injuries-emphasize an impairment that requires attention in the long-term rehabilitation of this clinical population, particularly in those with the lowest pulmonary function values. Previous studies report conflicting findings regarding whether FEV 1 /FVC and/or MVV is reduced in adults with well-healed burn injuries (Grisbrook et al, 2012;Özkal et al, 2021;Willis et al, 2011;Won et al, 2021). We did not find FEV 1 /FVC to be lower in our cohort, which is consistent with some (Özkal et al, 2021;Willis et al, 2011;Won et al, 2021), but not all (Grisbrook et al, 2012) prior work.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Together, these data-the most comprehensive assessment of pulmonary function among adults with well-healed burn injuries-emphasize an impairment that requires attention in the long-term rehabilitation of this clinical population, particularly in those with the lowest pulmonary function values. Previous studies report conflicting findings regarding whether FEV 1 /FVC and/or MVV is reduced in adults with well-healed burn injuries (Grisbrook et al, 2012;Özkal et al, 2021;Willis et al, 2011;Won et al, 2021). We did not find FEV 1 /FVC to be lower in our cohort, which is consistent with some (Özkal et al, 2021;Willis et al, 2011;Won et al, 2021), but not all (Grisbrook et al, 2012) prior work.…”
Section: Discussionsupporting
confidence: 69%
“…In adults with burn injuries assessed at discharge, the presence of an inhalation injury was associated with a lower FEV 1 /FVC (Özkal et al, 2021). In adults with burn injuries assessed three months after injury, those with an inhalation injury had a lower FEV 1 and FVC (Won et al, 2021). However, a retrospective assessment of long‐term lung function in patients with bronchoscopic evidence of smoke inhalation showed that combined inhalation injury and body surface burn do not necessarily imply long‐term damage to the respiratory airways or lungs (Bourbeau et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, full-thickness (i.e., severe) burn injuries that cover a significant portion of the body (e.g., >15% of total body surface area) and require prolonged hospitalization can contribute to lower pulmonary function for the remainder of their lives (5). Specifically, individuals who have sustained severe burn injuries have reduced forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC), maximal voluntary ventilation (MVV), forced expiratory flow at 25%–75% (FEF 25%–75% ), and lung diffusing capacity (4,6–14). In addition, our laboratory recently demonstrated that adults with well-healed burn injuries have reduced percent predicted FEV 1 , FEV 1 /FVC, FEF 25%–75% , and increased airway resistance decades after their burn injury (15).…”
mentioning
confidence: 99%
“…Specifically, individuals who have sustained severe burn injuries have reduced forced expiratory volume in 1 s (FEV 1 ), forced vital capacity (FVC), maximal voluntary ventilation (MVV), forced expiratory flow at 25%-75% (FEF 25%-75% ), and lung diffusing capacity (4,(6)(7)(8)(9)(10)(11)(12)(13)(14). In addition, our laboratory recently demonstrated that adults with well-healed burn injuries have reduced percent predicted FEV 1 , FEV 1 /FVC, FEF 25%-75% , and increased airway resistance decades after their burn injury (15).…”
mentioning
confidence: 99%